Building a virtualized environment for programming courses - Polvinen Tuisku; Ylikännö Timo; Mäkeläinen Ari; Rauti Sampsa; Mäkelä Jari-Matti; Tammi Jani (Germany, 2022)
Despite computer programming courses today often having hundreds of participants, it is important that the students complete practical programming exercises and have a possibility to participate in hands-on programming sessions, where they can get help from their peers and teaching assistants. However, heterogeneous devices used by students pose a great challenge. When installing and using development tools, both platform specific issues and the limitations of students' personal skill cause issues and lots of extra work for teachers. To address these challenges, we built a virtualized environment that provides the same homogeneous environment for all the students, reducing the time used for configuration and assisting students and allowing time to be used teaching the actual contents of the course. The current study provides an experience report on our course virtualization project, highlighting the drawbacks and benefits of our solution. Our preliminary findings indicate that vast majority of students are using the environment and have found it an effective and usable way to complete the practical coursework.
Trends and Innovations in Information Systems and Technologies: Volume 2